Graphene oxide/zinc ferrite nanocomposite loaded with doxorubicin as a potential theranostic mediu in cancer therapy and magnetic resonance imaging. Issue 8 (15th April 2022) - Ali, Rizwan; Aziz, Muhammad Hammad; Gao, Shuang; Khan, Muhammad Imran; Li, Fenfen; Batool, Tahira; Shaheen, Fozia; Qiu, Bensheng
Abstract: Hybrid functional biomaterials are attracting increasing interest due to their biocompatibility and therapeutic and diagnostic characteristics. The theranostic properties of functional biomaterials favor their application. When these materials are responded to stimuli, they confer target site delivery. Although various types of nanocomposites have been developed for drug delivery and diagnostics, no ideal composites have been reported yet. Here, we report the synthesis of graphene oxide–zinc ferrite hybrid nanocomposites (GO-ZnFe2 O4 ) conjugated with doxorubicin (GO-ZnFe2 O4 /DOX) for cancer therapy and magnetic resonance (MR) imaging-based diagnosis. The optical properties, crystal phase, particle size, functional groups, elemental composition, surface morphology, and magnetism of GO-ZnFe2 O4 nanocomposites were characterized using state-of-the-art available techniques, including Fourier-Transform Infrared Spectroscopy (FTIR), Ultraviolet visible spectroscopy (UV–Vis), Transmission electron microscopy (TEM), X-ray powder diffraction (XRD), Dynamic light scattering (DLS), Vibrating sample magneto meter (VSM) Scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and X-ray photoelectron spectra (XPS). The in vitro analysis showed that GO-ZnFe2 O4 conjugated with DOX is more cytotoxic than GO-ZnFe2 O4 . GO-ZnFe2 O4 /DOX induced the production of reactive oxygen species (ROS), which induced damage to nuclear DNA and mitochondrial DNA (mtDNA) when internalized by cells. This damage consequently drove mitochondrial malfunction and ultimately the apoptosis of cancer cells. Further studies were performed to investigate the diagnostic efficacy of these nanocomposites using MR imaging. GO-ZnFe2 O4 /DOX nanocomposites were developed and successfully employed in the MR imaging of HeLa cells. As shown in the present study, GO-ZnFe2 O4 /DOX might play a potential role in the development of chemotherapy and noninvasive MR imaging of tumor cells.